Laterality of visuo-spatial attention in acute and chronic schizophrenia, major depression and in healthy controls. - O'Carroll, R; Rogers, A; Lawrie, S; Murrary, C; Van Beck, M; Ebmeier, K; Walker, M; Blackwood, D; Johnstone, E; Goodwin, G (1995)
Previous studies have suggested that schizophrenia is characterized by an asymmetry of visuo-spatial attention, in particular that acute unmedicated schizophrenics demonstrate relative inattention to right hemispace, whereas chronically medicated patients demonstrate the opposite pattern. In the present study, 30 unmedicated schizophrenic patients, 32 chronically medicated schizophrenic patients, 30 patients suffering from major depression and 60 healthy controls were assessed using two measures of hemispatial attentional neglect, namely letter and star cancellation. The results demonstrated that the chronic schizophrenic group made more total omissions for star cancellation (in both right and left hemispace), but that there was no difference between the groups in terms of omission asymmetry for either letter or star cancellation.